2020
DOI: 10.1093/neuonc/noaa093
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modeling of glioblastoma initiation using PDGF-AA and p53-null neural progenitors

Abstract: Background Imagining ways to prevent or treat glioblastoma (GBM) has been hindered by a lack of understanding of its pathogenesis. Although overexpression of platelet derived growth factor with two A-chains (PDGF-AA) may be an early event, critical details of the core biology of GBM are lacking. For example, existing PDGF-driven models replicate its microscopic appearance, but not its genomic architecture. Here we report a model that overcomes this barrier to authenticity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…PDGF-A stimulation or overexpression and PDGF-B overexpression in glial or neural progenitors of mice have been demonstrated each acting a driver for gliomalike neoplasm or glioma-genesis in those mouse models [53][54][55]. However, their roles in the growth and malignancy of human glioma cells including GBM cell lines have not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-A stimulation or overexpression and PDGF-B overexpression in glial or neural progenitors of mice have been demonstrated each acting a driver for gliomalike neoplasm or glioma-genesis in those mouse models [53][54][55]. However, their roles in the growth and malignancy of human glioma cells including GBM cell lines have not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Although enrichment of ECM pathways was expected (3) given the invasive nature of LGAs, the prominence of the PDGF pathway was of interest because overexpression of PDGFA has been implicated in the etiology of IDH WT GBM (4) and the PDGFA ligand has been shown to initiate GBM in animal model systems (4,5).…”
Section: Enrichment Of the Pdgf Pathway And High Expression Of Pdgfa mentioning
confidence: 99%
“…Given the poor prognosis of IDH WT and PDGFA overexpressing LGAs, we then assessed additional biological features that might explain their propensity for GBM-like behavior. Having recently reported that in vitro exposure to PDGFA leads to chromosomal instability in neural progenitor cells (5) we assessed aneuploidy in LGAs in relation to IDH mutational status and PDGFA expression. In this analysis we observed that IDH WT LGAs were significantly more aneuploid than their IDH mutant counterparts (Fig.…”
Section: Pdgfa and Pdgfd Gene Expression And Idh Wt Status Are Associmentioning
confidence: 99%
See 2 more Smart Citations